A white low-carbon gelling material of lepidolite tailings and its preparation method and application
Through phosphoric acid pretreatment and thermal activation treatment, the problems of low gelation activity and whiteness of lithium mica tailings are solved, and the efficient resource utilization of lithium mica tailings in building materials manufacturing is achieved.
Patent Information
- Application Number
- CN202410984776.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-22
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-07-22
AI Technical Summary
Lithium mica tailings are produced during lithium mica extraction, and the prior art is difficult to effectively activate its gelling performance, and the high impurity content leads to low whiteness, which limits its application in building materials manufacturing.
The volcanic ash activity and whiteness of lithium mica tailings are improved by mixing with the phosphoric acid solution and granulating it and thermal activation at high temperature.
The gelling activity and whiteness of lithium mica tailings have been significantly improved, making it suitable for a wider range of building materials manufacturing, and is environmentally friendly and does not lead to corrosion of the performance of gelled hydration products.
Smart Images

Figure BDA0004957069600000111 
Figure HDA0004957069610000011 
Figure HDA0004957069610000012
Abstract
Description
Technical Field
[0001] The invention relates to the field of inorganic building materials, and in particular to a solid waste treatment method, and in particular to a resource treatment method for lepidolite tailings, and a method for preparing building materials by using the treated lepidolite tailings. Background Art
[0002] Lepidolite tailings are byproducts produced in the process of extracting lithium and its valuable metals from lepidolite minerals. In the process of extracting lithium from lepidolite, in addition to lepidolite concentrate and the final lithium carbonate product, tailings, lithium feldspar powder and tailings are also produced, which are collectively referred to as "slag" or "waste residue". These tailings are mainly composed of feldspar and quartz, but because feldspar and quartz are not effectively separated, the application market positioning of the product is unclear, and it can usually only be used in small quantities as a building material or stored. With the increase in lithium demand and the growth of lithium extraction from lepidolite, the environmental, safety and economic issues of tailings have become increasingly prominent, requiring corresponding treatment and comprehensive utilization.
[0003] With the advancement of science and technology, the treatment of low-activity solid wastes such as mine tailings has gradually changed from primitive landfill and storage to resource utilization. In the prior art, many studies have attempted to activate various tailings solid wastes, mainly including mechanical activation, thermal activation and chemical activation. Patent document CN 111847924 A discloses a method for activating lead-zinc tailings with quartz and dolomite as the main mineral components, which includes mechanical activation of grinding to a particle size of 200μm to 10μm, thermal activation at 400-600℃ and alkali activation in sequence; this method is not suitable for the activation of lithium mica tailings, and although the tailings have certain gelling properties after activation, the strength needs to be improved, and higher mechanical properties can only be obtained under autoclaving conditions. Patent document CN 112239331 A discloses an activation treatment method for muscovite tailings, kaolin tailings, and talc tailings, which mainly involves strong acid modification and calcination treatment; the hydrochloric acid, sulfuric acid, and nitric acid used in this method are highly polluting to the environment and have strong acidity, which seriously corrodes the equipment in the production process, and the product contains Cl - , sulfates and nitrates, which have a great impact on the performance of gelling hydration products. - Corrosion, sulfate corrosion and other adverse effects.
[0004] In addition to its low activity, lithium mica tailings also have the disadvantage of turning light yellow-brown when in contact with water due to the impurities they contain, which limits its scope of application and makes it difficult to use in the manufacture of building materials with high whiteness requirements.
[0005] Therefore, it is necessary to develop a new method for activating lithium mica tailings, which can not only effectively stimulate the activity of lithium mica tailings, but also increase its whiteness, so that the increasing lithium mica tailings have a higher resource utilization value. Summary of the invention
[0006] The primary purpose of the present invention is to provide a method for activating and treating lepidolite tailings, so as to significantly improve the gelling activity of lepidolite tailings, and to facilitate the resource utilization of lepidolite tailings in building materials.
[0007] Another object of the present invention is to provide a white low-carbon cementitious material prepared from the lepidolite tailings activated by the method of the present invention.
[0008] The above-mentioned object of the present invention is achieved by the following technical solutions:
[0009] In a first aspect, the present invention provides a method for activating and treating lepidolite tailings, comprising:
[0010] 1) Phosphoric acid pretreatment
[0011] The fine-grained lepidolite tailings and phosphoric acid solution are uniformly mixed in a mass ratio of 3-6:1 and then granulated to obtain particles with a diameter of 3-4 cm; the concentration of the phosphoric acid solution is 7-8 mol / L;
[0012] 2) Thermal activation
[0013] The particles obtained in 1) are subjected to high temperature treatment, firstly heated to 180-220° C. at a heating rate of 8-12° C. / min and kept warm for 3-5 hours, then heated to 700° C.-900° C. at a heating rate of 8-12° C. / min and kept warm for 1-3 hours; then quickly cooled to room temperature to obtain white activated lepidolite tailings.
[0014] In the method described in the present invention, the mineral composition of the lithium mica tailings is quartz, potassium, sodium feldspar and a small amount of white mica.
[0015] In a preferred embodiment of the present invention, the weight ratio of the fine-grained lepidolite tailings to the phosphoric acid solution is 4-5:1, and the concentration of the phosphoric acid solution is 7.5-7.8 mol / L; the most preferred concentration of the phosphoric acid solution is 7.56 mol / L.
[0016] In the method of the present invention, the thermal activation described in step 2) can cause the silicate minerals in the lithium mica tailings pretreated with phosphoric acid to undergo a phase transformation, and transform them into opal, cristobalite, zeolite, water kaolin and other minerals with high volcanic ash activity, and at the same time, the mineral crystal structure coordination of the lithium mica tailings can be changed through a high-temperature sintering process, and the pore structure can be eliminated, thereby changing the light absorption characteristics of the minerals and improving the whiteness of the tailings. In a preferred embodiment of the present invention, the thermal activation described in step 2) includes: first heating the particles to 180-200°C at a heating rate of 10°C / min for 3-5h, and then heating to 800°C-900°C at a heating rate of 10°C / min for 1-3h; more preferably, first heating the particles to 200°C at a heating rate of 10°C / min for 4h, and then heating to 800°C-900°C at a heating rate of 10°C / min for 2h.
[0017] In the preferred method of the present invention, the white activated lepidolite tailings are further mechanically activated, specifically, the active material obtained in 2) is crushed and ground for 20-80 minutes to obtain white activated lepidolite tailings powder. In a more preferred method, the grinding time is 60-80 minutes; most preferably, the grinding time is not less than 80 minutes until the specific surface area is 750-1300m 2 / kg. The mechanical activation can further enhance the gelling activity of the tailings.
[0018] In a second aspect, the present invention provides a white activated lepidolite tailings obtained by processing according to the method described in the first aspect.
[0019] The white activated lepidolite tailings have a whiteness of not less than 75%; and the mineral components thereof include opal, cristobalite, zeolite and hydrokaolin.
[0020] In the preferred embodiment of the present invention, the white activated lepidolite tailings have a specific surface area of 750-1300m 2 / kg of powder.
[0021] In the white activated lepidolite tailings described in the present invention, mineral components such as opal, cristobalite, zeolite, and water kaolin can provide relatively high volcanic ash activity, and the phosphorus-aluminum-silicon structure and the disordered active mineral structure formed under phosphoric acid treatment and thermal activation change the light absorption performance, thereby improving the whiteness of the tailings. The white activated lepidolite tailings described in the present invention have both relatively high gelling activity and whiteness, can be utilized as a building material raw material with a larger dosage, and have a wider range of applications.
[0022] In a third aspect, the present invention further provides a white gelling material, which is composed of a mixture of the white activated lepidolite tailings described in the second aspect of the present invention and a calcium salt excitation component.
[0023] In a preferred embodiment of the present invention, the calcium salt exciting component is selected from any one of Ca(OH)2, CaCl, CaSO4, CaO or a mixture of two or more thereof; preferably Ca(OH)2 and / or CaSO4.
[0024] In a preferred embodiment of the present invention, the mass ratio of the white activated lepidolite tailings to the calcium-containing excitation component is 6-8:2-4, more preferably 7-8:2-3, and most preferably 7-7.5:2.5-3.
[0025] Furthermore, the present invention also provides a white low-carbon gelling material of lepidolite tailings, the raw materials of which are composed of the white gelling material of the present invention and other gelling materials.
[0026] In a preferred embodiment of the present invention, the other cementitious materials are selected from any one or a combination of two or more of white cement, metakaolin, mineral powder or gypsum.
[0027] In a preferred embodiment of the present invention, the mass ratio of the white gelling material to other gelling materials is 6-8:2-4; more preferably 7-8:2-3; most preferably 7-7.5:2.5-3.
[0028] In a fourth aspect, the present invention further provides an application of the white low-carbon cementitious material of lithium mica tailings described in the third aspect in the preparation of cement. In the application, when the white low-carbon cementitious material of lithium mica tailings is mixed with water, a PCE polycarboxylate water reducer accounting for 0.5%-1% of the water mass is added.
[0029] The white low-carbon cementitious material of lithium mica tailings of the present invention is prepared based on the lithium mica tailings after activation treatment. During the activation treatment process, the lithium mica tailings are pretreated with phosphoric acid and thermally activated based on an amorphization activation method to release the volcanic ash activity of silicate minerals, and the main mineral components such as quartz and feldspar are converted into opal, cristobalite, zeolite, water kaolin and other minerals with high volcanic ash activity, and then crushed and ground to a specific surface area of 750-1300m 2 / kg, and then mixed with a calcium salt activator to have hydration gelling properties. After the mixture with hydration gelling properties is mixed with other cementitious materials of a specific type in a specific proportion, the obtained white low-carbon cementitious material will have abundant hydration products after the hydration reaction, including opal SiO2·xH2O, clinopyrite Ca2Al3(SiO4)(Si2O7)O(OH), hydrocalcium silicate Ca1.5SiO3.5·XH2O, hydroxycalcium silicate Ca4(SiO3)3(OH)3, orthorhombic calcium zeolite CaAl2Si2O8·4H2O, apatite CaAl2(PO4)2(OH)·2H2O, hydroxycalcium phosphate CaPO3(OH), etc. These hydration products can help cement obtain higher early strength and later strength.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The order of the activation treatment method of lepidolite tailings of the present invention is to first perform acidification pretreatment, and then perform high temperature thermal activation on the acidified tailings. In this process, the tailings DSC curve (such as Figure 1 As shown in Figure 2, the tailings after acidification undergo phase transformation at lower temperatures (60-80°C and 180-200°C) to form a new phosphate mineral phase, hydrophosphate calcium potassium stone K3Na2Ca 10 Al 15 PO421(OH)7·26H2O, and there is a continuous thermodynamic phase transition zone in the high temperature zone (700-900℃), which provides a thermodynamic basis for preventing mineral recrystallization and activity elimination in the subsequent thermal activation process, and is conducive to the generation of more disordered, amorphous mineral components with volcanic ash activity.
[0032] 2. In the activation treatment method of lithium mica tailings described in the present invention, weakly acidic phosphoric acid is used for pretreatment. After phosphoric acid activation, the excess phosphoric acid will react with the subsequently compounded calcium-based activator to form calcium phosphate, and calcium phosphate is a stable gel structure that is beneficial to the hydration product and structural performance. Compared with the existing method of using strong acid to treat tailings, the present invention is more friendly to the environment and equipment, and will not bring Cl to the performance of the gel hydration product. - Corrosion or sulfate corrosion, the generated calcium phosphate is more conducive to improving hydration products and structural properties.
[0033] 3. In the activation treatment method of the lepidolite tailings of the present invention, phosphoric acid pretreatment and thermal activation can also significantly improve the whiteness of the lepidolite tailings raw material. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The DSC curves of lithium mica tailings before phosphoric acid pretreatment (Fw) and after phosphoric acid pretreatment (Fwp).
[0035] Figure 2 This is the XRD diagram of the lithium mica tailings used as the raw material in Example 1.
[0036] FIG3( a ) shows the appearance of the lithium mica tailings used as the raw material in Example 1.
[0037] FIG3( b ) shows the appearance morphology of the active raw material of the lithium mica tailings after acid-heat activation in Example 1.
[0038] FIG3( c ) shows the appearance of the lithium mica tailings powder obtained in Comparative Example 1.
[0039] FIG3( d ) shows the appearance of the white activated lepidolite tailings powder obtained in Example 1.
[0040] Figure 4 It is the XRD diagram of the lithium mica tailing volcanic ash active raw material AI of Example 1 and the lithium mica tailing raw material D-1 of Comparative Example 1.
[0041] Figure 5 It is the XRD diagram of the white low-carbon cementitious material C-2 from the lepidolite tailings of Example 8 and the white low-carbon cementitious material C-7 from the lepidolite tailings of Example 13.
[0042] Figure 6 The early strength of the cementitious materials prepared in Examples 7, 8, 16, 17, 18, 19, 20 and 21 after hydration is reflected.
[0043] Figure 7 The results show that the late strength of the cementitious materials prepared in Examples 7, 8, 16, 17, 18, 19, 20 and 21 after hydration.
[0044] Figure 8 The results show that the early strength of the cementitious materials prepared in Comparative Examples 6, 7, 9, 10, 11, 12, 13 and 14 after hydration.
[0045] Fig. 9 The results show that the later strength of the cementitious materials prepared in Comparative Examples 6, 7, 9, 10, 11, 12, 13 and 14 after hydration.
[0046] Fig.10 It reflects the appearance of the lithium mica tailings gel material F-3 of comparative example 8 after hydration. DETAILED DESCRIPTION
[0047] The technical scheme and technical effects of the present invention will be described in detail below by listing embodiments and experimental examples.
[0048] Before describing the present invention in detail below, it should be understood that the present invention is not limited to the specific methods, protocols and reagents described herein, as they may vary. It should also be understood that the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of the present invention, which is limited only by the appended claims. Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art are generally understood.
[0049] First, the present invention provides an activation treatment method for lepidolite tailings, which can also be called a method for preparing active volcanic ash active raw materials from lepidolite tailings, which can be the following specific implementation scheme:
[0050] The lithium mica tailings are screened, and the fine-grained tailings below 0.15 mm are used as raw materials for standby use. 100 parts by mass of the lithium mica tailings are evenly mixed with 20-30 parts of 7-8 mol / L phosphoric acid solution, and then granulated into blocks with a diameter of 3-4 cm. The blocks are placed in a high-temperature furnace and heated to 180-220°C at a rate of 8-12°C / min for 3-5 hours, and then heated to 800°C-900°C at a rate of 8-10°C / min for 1-3 hours, and then quickly cooled to room temperature. The high-temperature activated lithium mica tailings active material is crushed into particles below 2 mm by a crusher, and mechanically ground to 750-800m with ceramic balls. 2 / kg, to obtain the active raw material of lithium mica tailings volcanic ash.
[0051] On this basis, the present invention also provides a method for preparing a white gelling material based on the above-mentioned activated lepidolite tailings, which can be the following specific implementation scheme:
[0052] By weight, 70-80 parts of the lithium mica tailings volcanic ash active raw material prepared by the above method and 20-30 parts of a calcium salt activator (selected from any one or more mixtures of Ca(OH)2, CaCl, CaSO4, and CaO) are mixed uniformly to obtain a premix;
[0053] Furthermore, by weight, 70-80 parts of the premix and 20-30 parts of other cementitious materials (selected from any one or more mixtures of 52.5 white cement, metakaolin, mineral powder, and gypsum) are evenly mixed to obtain a white low-carbon cementitious material of lithium mica tailings.
[0054] According to the above method, specific embodiments and experimental examples are provided as follows:
[0055] Example 1.
[0056] A method for preparing volcanic ash active raw materials from lepidolite tailings, the specific steps are as follows:
[0057] The raw material is lithium mica tailings from Yichun area, with quartz, potassium feldspar and sodium feldspar as the main mineral components. Its XRD pattern is as follows Figure 2 As shown, the appearance is shown in Figure 3(a);
[0058] The lepidolite tailings are screened, and the fine-grained tailings below 0.15 mm are used as raw materials for standby use. 100 parts by mass of the lepidolite tailings are mixed with 20 parts by mass of a 7.56 mol / L phosphoric acid solution, and then granulated into blocks with a diameter of 3-4 cm;
[0059] The block was placed in a high temperature furnace and heated to 200°C at a rate of 10°C / min and kept at that temperature for 4 hours, and then heated to 800°C at a rate of 10°C / min and kept at that temperature for 2 hours, and then quickly cooled to room temperature to obtain the active raw material of lithium mica tailings after acid-heat activation; its appearance is shown in Figure 3(b);
[0060] The active raw materials of lithium mica tailings after acid-heat activation are crushed into particles below 2 mm by a crusher, and then mechanically ground with ceramic balls for 80 minutes to 750-800 mm 2 / kg, a white activated lepidolite tailings powder (lepidolite tailings volcanic ash active raw material AI) was obtained, and its appearance is shown in Figure 3(d).
[0061] Example 2.
[0062] A method for preparing active volcanic ash active raw materials from lepidolite tailings, the specific steps are as follows:
[0063] Take the same lepidolite tailing as Example 1 as raw material, sieve the lepidolite tailing, the fine-grained tailings below 0.15mm are used as raw material for standby, 100 parts by mass of lepidolite tailings are mixed with 30 parts of 7.56mol / L phosphoric acid solution and then granulated into a block with a diameter of 3-4cm, put it into a high-temperature furnace and heat it to 200°C at a speed of 10°C / min for 4h, then heat it to 900°C at a speed of 10°C / min for 2h and then quickly cool it to room temperature, the high-temperature activated lepidolite tailing active material is crushed to particles below 2mm with a crusher, and mechanically ground with ceramic balls for 80min to 750-800m 2 / kg, and obtain white activated lepidolite tailings powder (lepidolite tailings volcanic ash active raw material A-II).
[0064] Example 3.
[0065] A method for preparing active volcanic ash active raw materials from lepidolite tailings, the specific steps are as follows:
[0066] Take the same lepidolite tailing as Example 1 as raw material, sieve the lepidolite tailing, the fine-grained tailings below 0.15mm are used as raw material for standby, granulate into a block with a diameter of 3-4cm after 100 parts by mass of lepidolite tailings and 25 parts of 7.56mol / L phosphoric acid solution are mixed evenly, put into a high-temperature furnace and heat to 200°C and keep incubated for 4h at a speed of 10°C / min, then heat to 850°C and keep incubated for 2h at a speed of 10°C / min and then quickly cool to room temperature, the high-temperature activated lepidolite tailing active material is crushed to particles below 2mm with a crusher, and mechanically ground with ceramic balls for 80min to 750-800m 2 / kg, and obtain white activated lepidolite tailings powder (lepidolite tailings volcanic ash active raw material A-III).
[0067] Example 4-Example 6.
[0068] The active raw material of lithium mica tailings volcanic ash was prepared by referring to the method of Example 1, except that the mechanical grinding time of ceramic balls was changed to 20 min, 40 min and 60 min, respectively, to obtain lithium mica tailings volcanic ash active raw materials A-IV, AV and A-VI with different specific surface areas.
[0069] Comparative Example 1.
[0070] Take the same lithium mica tailings as in Example 1 as raw material, without the acid-heat activation treatment described in Example 1, directly crush it into particles below 2 mm with a crusher, and grind it mechanically with ceramic balls for 80 min to 750-800 mm 2 / kg, a light yellow lithium mica tailings powder (lithium mica tailings raw material D-1) was obtained, and its appearance is shown in Figure 3(c).
[0071] Comparative Example 2.
[0072] The same lithium mica tailings as in Example 1 were used as raw materials, and the same phosphoric acid pretreatment as in Example 1 was used, but a different thermal activation treatment process was used, including rapid heating to 600°C and keeping the temperature for 2 hours. After cooling to room temperature, the tailings were crushed to particles less than 2 mm using a crusher, and mechanically ground with ceramic balls for 80 minutes to 750-1300 mm. 2 / kg, and obtained activated lepidolite tailings powder (lepidolite tailings raw material D-2). It was found through testing that the active hydrated metakaolin, phosphate quartz and cristobalite phases obtained from its mineral components were less, and the hardened slurry strength was lower than that of the lepidolite tailings volcanic ash active raw material AI prepared in Example 1.
[0073] Comparative Example 3-Comparative Example 5.
[0074] The lithium mica tailings powder was prepared by referring to the method of Comparative Example 1, except that the mechanical grinding time of the ceramic balls was changed to 20 min, 40 min and 60 min, respectively, to obtain lithium mica tailings raw materials D-3, D-4 and D-5 with different specific surface areas.
[0075] Example 7.
[0076] A method for preparing a white gelling material from lepidolite tailings, comprising the following specific steps:
[0077] By weight, 70 parts of the lithium mica tailings volcanic ash active raw material AI prepared in Example 1 and 30 parts of Ca(OH)2 were mixed uniformly to form a premix B-1.
[0078] By weight, 75 parts of the premix and 25 parts of 52.5 white cement were added to obtain a white low-carbon cementitious material C-1 made of lepidolite tailings.
[0079] Example 8.
[0080] A method for preparing a white gelling material from lepidolite tailings, comprising the following specific steps:
[0081] By weight, 70 parts of the lithium mica tailings volcanic ash active raw material AI prepared in Example 1 were uniformly mixed with 25 parts of Ca(OH)2 and 5 parts of CaSO4 to form a premix B-2.
[0082] By weight, 75 parts of the premix and 25 parts of 52.5 white cement were added to obtain a white low-carbon cementitious material C-2 made of lepidolite tailings.
[0083] Example 9.
[0084] A method for preparing a white gelling material from lepidolite tailings, comprising the following specific steps:
[0085] By weight, 80 parts of the lithium mica tailings volcanic ash active raw material AI prepared in Example 1 and 20 parts of Ca(OH)2 were mixed uniformly to form a premix B-3.
[0086] By weight, 70 parts of the premix and 30 parts of 52.5 white cement were added to obtain a white low-carbon cementitious material C-3 made of lepidolite tailings.
[0087] Example 10.
[0088] A method for preparing a white gelling material from lepidolite tailings, comprising the following specific steps:
[0089] By weight, 75 parts of the lithium mica tailings volcanic ash active raw material AI prepared in Example 1 were uniformly mixed with 20 parts of Ca(OH)2 and 5 parts of CaSO4 to form a premix B-4.
[0090] By weight, 70 parts of the premix and 30 parts of 52.5 white cement were added to obtain a white low-carbon cementitious material C-4 made of lepidolite tailings.
[0091] Example 11.
[0092] A method for preparing a white gelling material from lepidolite tailings, comprising the following specific steps:
[0093] By weight, 80 parts of the lithium mica tailings volcanic ash active raw material A-II prepared in Example 2 and 20 parts of Ca(OH)2 were mixed evenly to form a premix B-5.
[0094] By weight, 70 parts of the premix and 30 parts of 52.5 white cement were added to obtain the lepidolite tailings white low-carbon cementitious material C-5.
[0095] Example 12.
[0096] A method for preparing a white gelling material from lepidolite tailings, comprising the following specific steps:
[0097] By weight, 80 parts of the lithium mica tailings volcanic ash active raw material A-II prepared in Example 2 were uniformly mixed with 15 parts of Ca(OH)2 and 5 parts of CaO to form a premix B-6.
[0098] By weight, 70 parts of the premix and 30 parts of 52.5 white cement were added to obtain a white low-carbon cementitious material C-6 made of lepidolite tailings.
[0099] Example 13.
[0100] A method for preparing a white gelling material from lepidolite tailings, comprising the following specific steps:
[0101] By weight, 80 parts of the lithium mica tailings volcanic ash active raw material A-II prepared in Example 2 were uniformly mixed with 15 parts of Ca(OH)2 and 5 parts of CaO to form a premix B-7.
[0102] By weight, 70 parts of the premix are mixed with 20 parts of 52.5 white cement, 5 parts of mineral powder and 5 parts of gypsum to obtain a white low-carbon cementitious material C-7 made of lepidolite tailings.
[0103] Example 14.
[0104] A method for preparing a white gelling material from lepidolite tailings, comprising the following specific steps:
[0105] By weight, 75 parts of the lithium mica tailings volcanic ash active raw material A-III prepared in Example 3 and 25 parts of Ca(OH)2 were mixed uniformly to form a premix B-8.
[0106] By weight, 75 parts of the premix and 25 parts of 52.5 white cement were added to obtain the white low-carbon cementitious material C-8 made of lepidolite tailings.
[0107] Example 15.
[0108] A method for preparing a white gelling material from lepidolite tailings, comprising the following specific steps:
[0109] By weight, 75 parts of the lithium mica tailings volcanic ash active raw material A-III prepared in Example 3 and 25 parts of CaO were uniformly mixed to form a premix B-9.
[0110] By weight, 70 parts of the premix, 22 parts of 52.5 white cement, 5 parts of metakaolin and 3 parts of gypsum were uniformly mixed to obtain a white low-carbon cementitious material C-9 made of lepidolite tailings.
[0111] Example 16-Example 18.
[0112] A white cementitious material is prepared using lepidolite tailings by referring to the method of Example 9, except that the lepidolite tailings volcanic ash active raw material AI prepared in Example 1 is replaced by lepidolite tailings volcanic ash active raw materials A-IV, AV and A-VI prepared in Examples 4 to 6, respectively, to obtain lepidolite tailings white low-carbon cementitious materials C-10, C-11 and C-12.
[0113] Example 19-Example 21.
[0114] A white cementitious material is prepared using lepidolite tailings by referring to the method of Example 10, except that the lepidolite tailings volcanic ash active raw material AI prepared in Example 1 is replaced by lepidolite tailings volcanic ash active raw materials A-IV, AV and A-VI prepared in Examples 4 to 6, respectively, to obtain lepidolite tailings white low-carbon cementitious materials C-13, C-14 and C-15.
[0115] Comparative Example 6.
[0116] By weight, 80 parts of the lithium mica tailings raw material D-1 prepared in Comparative Example 1 were taken and mixed evenly with 20 parts of Ca(OH)2 to form a premix E-1.
[0117] By weight, 70 parts of the premix and 30 parts of 52.5 white cement were mixed to obtain the lepidolite tailings cementitious material F-1.
[0118] Comparative Example 7.
[0119] By weight, 75 parts of the lithium mica tailings raw material D-1 prepared in Comparative Example 1 were mixed evenly with 20 parts of Ca(OH)2 and 5 parts of CaSO4 to form a premix E-2.
[0120] By weight, 70 parts of the premix and 30 parts of 52.5 white cement were added to obtain the lepidolite tailings cementitious material F-2.
[0121] Comparative Example 8.
[0122] By weight, 80 parts of the lithium mica tailings raw material AI prepared in Example 1 were taken and mixed evenly with 20 parts of NaOH to form a premix E-3.
[0123] By weight, 70 parts of the premix and 30 parts of 52.5 white cement were added to obtain the lepidolite tailings cementitious material F-3.
[0124] Comparative Example 9-Comparative Example 11.
[0125] A white gelling material was prepared using lepidolite tailings by referring to the method of Comparative Example 6, except that the lepidolite tailings raw material D-1 prepared in Comparative Example 1 was replaced by lepidolite tailings raw materials D-3, D-4 and D-5 prepared in Comparative Examples 3 to 5, respectively, to obtain lepidolite tailings gelling materials F-4, F-5 and F-6.
[0126] Comparative Example 12-Comparative Example 14.
[0127] The method of Comparative Example 7 is used to prepare a cementitious material using lepidolite tailings, except that the lepidolite tailings raw material D-1 prepared in Comparative Example 1 is replaced by lepidolite tailings raw materials D-3, D-4 and D-5 prepared in Comparative Examples 3 to 5, respectively, to obtain lepidolite tailings cementitious materials F-7, F-8 and F-9.
[0128] Experimental example 1.
[0129] The active raw material AI of the lithium mica tailings volcanic ash prepared in Example 1 and the lithium mica tailings raw material D-1 prepared in Comparative Example 1 were tested by X-ray diffractometer, and the obtained XRD results are as follows: Figure 4 As shown. Figure 4 It can be seen that compared with the lithium mica tailings raw material D-1 prepared in Comparative Example 1, the lithium mica tailings volcanic ash active raw material AI prepared in Example 1 contains a large amount of sodium clinozeolite, opal, quartz and water kaolin.
[0130] Experimental example 2.
[0131] Take the white low-carbon cementitious material C-2 from lithium mica tailings prepared in Example 8, the white low-carbon cementitious material C-7 from lithium mica tailings prepared in Example 13, and the white low-carbon cementitious material C-9 from lithium mica tailings prepared in Example 15, and mix them with water respectively. During mixing, add 0.5wt%-1wt% of PCE polycarboxylic acid water reducer and mix well with the aqueous solution, then stir evenly to obtain a series of cement test blocks, and then cure and test the performance.
[0132] According to GB / T 1346 "Standard water consumption, setting time and stability test method for cement" and GB / T 17671 "Test method for strength of cement mortar (ISO method)", the final setting time, fluidity, 7-day compressive strength and 28-day compressive strength of the above cement test blocks were measured. The test results are shown in Table 1:
[0133] Table 1. Performance of 0.35w / s lepidolite tailings white low-carbon cementitious materials of Example 8, Example 13, and Example 15
[0134]
[0135] Note: The fluidity is tested using a cylinder with a diameter of 30 mm.
[0136] It can be seen from Table 1 above that the gelling materials prepared in Examples 8, 13 and 15 of the present invention all have excellent gelling properties and mechanical strength after hydration.
[0137] In addition, the two cement test blocks prepared from the above C-2 and C-7 cementitious materials were tested by X-ray diffractometer, and it was found that there were abundant hydration products after the hydration reaction. The XRD results are as follows: Figure 5 As shown. Figure 5 It can be seen that the hydration products include opal SiO2·xH2O, clinodite Ca2Al3(SiO4)(Si2O7)O(OH), hydrocalcium hydrate Ca1.5SiO3.5·XH2O, hydroxycalcium hydrate Ca4(SiO3)3(OH)3, orthorhombic zeolite CaAl2Si2O8·4H2O, apatite CaAl2(PO4)2(OH)·2H2O, hydroxycalcium phosphate CaPO3(OH) and many others.
[0138] Experimental Example 3.
[0139] The cementitious materials prepared in Examples 7, 8, 16, 17, 18, 19, 20 and 21 were mixed with water respectively. During mixing, 0.5wt%-1wt% of PCE polycarboxylate water reducer was added and mixed evenly with the aqueous solution, and then stirred evenly to obtain a series of cement test blocks. The 7-day compressive strength and 28-day compressive strength were measured according to GB / T 17671 "Test Method for Strength of Cement Mortar (ISO Method)". The test results are as follows: Figure 6-Figure 7 shown.
[0140] The cementitious materials prepared in Comparative Examples 6, 7, 9, 10, 11, 12, 13 and 14 were mixed with water respectively. During mixing, 0.5wt%-1wt% of PCE polycarboxylate water reducer was added and mixed evenly with the aqueous solution, and then stirred evenly to obtain a series of cement test blocks. The 7-day compressive strength and 28-day compressive strength were measured according to GB / T 17671 "Test Method for Strength of Cement Mortar (ISO Method)". The test results are as follows: Figure 8-Figure 9 shown.
[0141] First, through Figure 6-Figure 7 and Figure 8-Figure 9 Comparison of the corresponding groups shows that, under the same grinding time and activator, the early and late strengths of the lepidolite tailings treated by the method of the present invention after hydration are significantly improved compared with the lepidolite tailings not treated by the method of the present invention. In other words, the acid-heat activation of the present invention will bring higher volcanic ash activity to the lepidolite tailings.
[0142] On this basis, through Figure 6-Figure 7It can be seen that after the lithium mica tailings are activated by acid-heat in the present invention, their early strength and late strength will be further improved with the extension of grinding time. 2 / kg, after further mixing with Ca(OH)2 or Ca(OH)2 composite CaSO4 activator, it can react with water to produce gelling hardening, and the 7d strength can reach 13MPa, and the 28d strength can reach 13.2MPa. Under the action of alkali activator, the mechanical properties increase rapidly at 7d, and the mechanical properties increase slowly from 7d to 28d, mainly because the alkali activator cannot continuously support the alkali activating reaction after a large amount of consumption. Therefore, no less than 20wt% white cement component is used for composite strengthening, and the alkalinity of the late gelling system and the continuous increase of late strength are increased through the cement hydration process.
[0143] Furthermore, through Figure 6 Comparison between the groups shows that although both the early strength and the late strength increase with the extension of the grinding time, the early stimulation effects of different calcium salt activators under the same grinding conditions are significantly different. When the Ca(OH)2 activator is added alone after the acid-heat activation treatment of the present invention, a very short grinding time can bring higher early strength, and the 7d strength of 20min grinding can reach 6.8MPa, and after the grinding time reaches 40min, the 7d strength can be higher than 9.0MPa; however, when the Ca(OH)2 and CaSO4 composite activator is added after the acid-heat activation treatment of the present invention, the 7d strength is significantly lower than the case of adding the Ca(OH)2 activator alone when the grinding time is short (20min-40min), and the 7d strength does not reach or even exceed the case of adding the Ca(OH)2 activator alone until the grinding time is longer than 60min.
[0144] Experimental Example 4.
[0145] The lithium mica tailings cementitious material F-3 prepared in Comparative Example 8 was mixed with water. During the mixing process, 0.5wt%-1wt% of PCE polycarboxylate water reducer was added to the aqueous solution and mixed evenly. The obtained sample was muddy and could not be formed. Its appearance was as follows: Fig.10 shown.
Claims
1. A method for activating and treating lepidolite tailings, characterized in that: include: 1) Phosphoric acid pretreatment The fine-grained lepidolite tailings and phosphoric acid solution are uniformly mixed in a mass ratio of 3-6:1 and then granulated to obtain particles with a diameter of 3-4 cm; the concentration of the phosphoric acid solution is 7-8 mol / L; 2) Thermal activation The particles obtained in 1) are subjected to high temperature treatment, firstly heated to 180-220°C at a heating rate of 8-12°C / min and kept warm for 3-5h, then heated to 700°C-900°C at a heating rate of 8-12°C / min and kept warm for 1-3h; then quickly cooled to room temperature to obtain white activated lepidolite tailings.
2. The method according to claim 1, characterized in that: The weight ratio of the fine-grained lepidolite tailings to the phosphoric acid solution is 4-5:1, and the concentration of the phosphoric acid solution is 7.5-7.8 mol / L.
3. The method according to claim 1, characterized in that: The weight ratio of the fine-grained lithium mica tailings to the phosphoric acid solution is 4-5:1, and the concentration of the phosphoric acid solution is 7.56 mol / L.
4. The method according to claim 1, characterized in that Step 2) The thermal activation comprises: firstly heating the particles to 180-200°C at a heating rate of 10°C / min and keeping the temperature for 3-5h, and then heating to 800-900°C at a heating rate of 10°C / min and keeping the temperature for 1-3h.
5. The method according to claim 1, characterized in that The thermal activation in step 2) comprises: firstly heating the particles to 200°C at a heating rate of 10°C / min and keeping the temperature for 4 hours, and then heating the particles to 800°C-900°C at a heating rate of 10°C / min and keeping the temperature for 2 hours.
6. The method according to claim 1, characterized in that: The method further comprises mechanically activating the white activated lepidolite tailings, specifically, crushing the active material obtained in 2) and grinding it for 20-80 minutes to obtain white activated lepidolite tailings powder.
7. The method according to claim 6, characterized in that: The grinding time is 60-80 min until the specific surface area reaches 750-1300m 2 / kg.
8. A white activated lepidolite tailing obtained by the method according to any one of claims 1 to 7, characterized in that: The white activated lepidolite tailings have a whiteness of not less than 75%; and the mineral components thereof include opal, cristobalite, zeolite and hydrokaolin.
9. The white activated lepidolite tailings as claimed in claim 8, characterized in that: The white activated lepidolite tailings have a specific surface area of 750-1300m 2 / kg of powder.
10. A white gelling material, which is composed of a mixture of the white activated lepidolite tailings according to any one of claims 8 to 9 and a calcium salt excitation component.
11. The white gelling material according to claim 10, characterized in that: The calcium salt exciting component is selected from any one of Ca(OH)2, CaCl, CaSO4, CaO or a mixture of two or more thereof.
12. The white gelling material according to claim 10, characterized in that: The calcium salt exciting component is selected from Ca(OH)2 and / or CaSO4.
13. The white gelling material according to any one of claims 10 to 12, characterized in that: The mass ratio of the white activated lepidolite tailings to the calcium-containing excitation component is 6-8:2-4.
14. The white gelling material according to any one of claims 10 to 12, characterized in that: The mass ratio of the white activated lepidolite tailings to the calcium-containing exciting component is 7-8:2-3.
15. The white gelling material according to any one of claims 10 to 12, characterized in that: The mass ratio of the white activated lepidolite tailings to the calcium-containing exciting component is 7-7.5:2.5-3.
16. A white low-carbon gelling material of lepidolite tailings, characterized by: The raw materials are composed of the white gelling material described in any one of claims 10 to 15 and other gelling materials.
17. The white low-carbon gelled material of lepidolite tailings according to claim 16, characterized in that: The other cementitious materials are selected from any one of white cement, metakaolin, mineral powder or gypsum, or a combination of two or more thereof.
18. The white low-carbon cementitious material of lepidolite tailings according to any one of claims 16 to 17, characterized in that: The mass ratio of the white gelling material to other gelling materials is 6-8:2-4.
19. The white low-carbon cementitious material of lepidolite tailings according to any one of claims 16 to 17, characterized in that: The mass ratio of the white gelling material to other gelling materials is 7-8:2-3.
20. The white low-carbon cementitious material of lepidolite tailings according to any one of claims 16 to 17, characterized in that: The mass ratio of the white gelling material to other gelling materials is 7-7.5:2.5-3.
21. Use of the white low-carbon cementitious material of lepidolite tailings according to any one of claims 16 to 20 in the preparation of cement, wherein when the white low-carbon cementitious material of lepidolite tailings is mixed with water, a PCE polycarboxylate water reducer accounting for 0.5% to 1% of the mass of the water is added.
Citation Information
Patent Citations
Tailing-based cementing material and preparation method thereof
CN111847924A
Multi-solid-waste early-strength cement and preparation method thereof
CN112239331A
Modified lithium slag composite mineral admixture and preparation and application thereof
CN112079589A
Roadbed water-stable layer prepared from lithium slag synergistically-activated squeezed fine silt and preparation method of roadbed water-stable layer
CN116375406A